2021
DOI: 10.1038/s41598-021-96898-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling and experimental verification of thermal effects in living cells exposed to high-power pulses of THz radiation

Abstract: Exposure of cells or biological tissues to high-power pulses of terahertz (THz) radiation leads to changes in a variety of intracellular processes. However, the role of heating effects due to strong absorption of THz radiation by water molecules still stays unclear. In this study, we performed numerical modelling in order to estimate the thermal impact on water of a single THz pulse as well as a series of THz pulses. A finite-element (FE) model that provides numerical solutions for the heat conduction equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, our previous findings [34] demonstrated the absence of reactive oxygen species and the oxidative stress in cells under THz exposure. It was also shown [48] that cell heating effect due to exposure of fibroblasts to THz radiation with average power of 1.5 mW…”
Section: Fibroblastsmentioning
confidence: 97%
“…However, our previous findings [34] demonstrated the absence of reactive oxygen species and the oxidative stress in cells under THz exposure. It was also shown [48] that cell heating effect due to exposure of fibroblasts to THz radiation with average power of 1.5 mW…”
Section: Fibroblastsmentioning
confidence: 97%
“…Thus, the irradiation time of cell cultures of t = 0.5 h was chosen. The estimations performed earlier showed that the thermal treatment of the cell culture is minimal, and the temperature elevation at the spot of the THz treatment does not exceed 2.8 °C [ 62 ]. The size of the irradiated area of cells was determined by the size of the focused beam, i.e., ~480 µm at the 1/ e level.…”
Section: Methodsmentioning
confidence: 99%
“…THz radiation is nonionizing, and the rays can penetrate paper, plastic, and up to 300 µm in the human skin [ 1 ]. Due to the influence of THz radiation on the vibration of atomic groups in macromolecules and on hydrogen bonds, heating is expected to occur upon irradiation [ 2 , 3 ]. With low photon energies, THz radiation is considered safe for humans because it is nonionizing (e.g., 1 THz photon energy <0.004 eV).…”
Section: Introductionmentioning
confidence: 99%
“…However, exposure to relatively large energy levels can be harmful because of the thermal effects. Even so, the maximal increase in temperature observed in primary human skin fibroblasts treated with THz pulsed radiation (1.5 THz, power P = 1.5 mW, intensity I = 0.83 W/cm 2 , t = 1000 s) was only 0.7 °C [ 3 ]. Upon irradiation (2.7 THz, I = 260 mW/cm 2 , t = 30 min) of the skin of a living mouse, no heating of the tissue was detected [ 4 ].…”
Section: Introductionmentioning
confidence: 99%